Electrochemical Energy Conversion and Storage with Zeolitic Imidazolate Framework Derived Materials: A Perspective. Issue 23 (25th October 2018) - Dutta, Soumen; Liu, Zhiming; Han, HyukSu; Indra, Arindam; Song, Taeseup
Abstract: The development of transition‐metal‐based materials for electrochemical energy conversion and storage has received immense interest throughout the last two decades. In this respect, zeolitic imidazolate framework (ZIF)‐derived materials are particularly important for accessing various morphologies, sizes, exposed facets, variations in the electronic structure, high surface area, and large numbers of available active sites. The properties of the ZIF‐derived materials can be tuned by applying different synthetic protocols, introducing a heteroatom in the ZIF structure or by accessing core‐shell or hollow structures. Many studies have described the beneficial effects of ZIF‐derived materials, but no critical review is available in the growing field of electrochemical energy conversion and storage. Herein, we have described the basic principles of material synthesis from ZIFs, their applications in electrochemical processes, difficulties with the synthesis, and their future development. Abstract : Frame of view : Structural, morphological and electronic structure development of zeolitic imidazolate framework (ZIF)‐derived materials for electrochemical energy conversion and storage are reviewed.